White Leaf Spot Caused by Neopseudocercosporella capsellae: A Re-emerging Disease of Brassicaceae - Gunasinghe, Niroshini; Barbetti, Martin J.; You, Ming Pei; Burrell, Daniel; Neate, Stephen (Frontiers in Cellular and Infection Microbiology, 2020)
White leaf spot can cause significant damage to many economically important Brassicaceae crops, including oilseed rape, vegetable, condiment, and fodder Brassica species, and recently has been identified as a re-emerging disease. The causal agent, Neopseudocercosporella capsellae, produces foliar, stem, and pod lesions under favourable weather conditions. The pathogen, N. capsellae secretes cercosporin, a non-host specific, photo-activated toxin, into the host tissue during the early infection process. The pathogen has an active parasitic stage on the living host and a sexual or asexual saprobic stage on the dead host. Where the sexual stage exists, ascospores initiate the new disease cycle, while in the absence of the sexual stage, conidia produced by the asexual stage initiate new disease cycles. Distribution of the pathogen is worldwide; however, epidemiology and disease severity differ between countries or continents, with it being more destructive in Subtropical, Mediterranean, or Temperate climate regions with cool and wet climates. The pathogen has a wide host range within Brassicaceae. Brassica germplasm show varied responses from highly susceptible to completely resistant to pathogen invasion and significant susceptibility differences are observed among major crop species. Cultural practices only provide effective disease control when the climate is not conducive. An increase in the susceptible host population and favourable weather conditions have together favoured the recent rise in white leaf spot disease occurrence and spread. The lack of understanding of variation in pathogen virulence and associated resistant gene sources within brassicas critically limits the potential to develop efficient control measures.